2006
DOI: 10.1007/s00299-006-0217-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of genetic transformation in Morus alba L. via different regeneration systems

Abstract: Three different regeneration systems, viz. direct regeneration of adventitious shoot buds from explant, regeneration through callus cultures and somatic embryos were compared to see their effect on transfer of neomycin phosphotransferase (nptII) and beta-glucuronidase (GUS) reporter gene (gus) to Morus alba clone M5, through Agrobacterium tumefaciens mediated transformation. Pre-conditioning and co-cultivation durations had a marked effect on transformation frequency. The highest transformation frequency of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…The osmotin gene construct was introduced into mulberry by Agrobacterium-mediated transformation using different mulberry explants and regenerative callus tissue. A number of prior reports describe the use of regenerative callus for the transformation in mulberry (Nozue et al 2000;Aggarwal and Kanwar 2006), but the efficiency of transformation was low in these studies. In contrast, in our Inducible expression by the rd29A promoter…”
Section: Osmotin Overexpression By the Camv 35s Promotermentioning
confidence: 91%
“…The osmotin gene construct was introduced into mulberry by Agrobacterium-mediated transformation using different mulberry explants and regenerative callus tissue. A number of prior reports describe the use of regenerative callus for the transformation in mulberry (Nozue et al 2000;Aggarwal and Kanwar 2006), but the efficiency of transformation was low in these studies. In contrast, in our Inducible expression by the rd29A promoter…”
Section: Osmotin Overexpression By the Camv 35s Promotermentioning
confidence: 91%
“…In the present studies we found that roots developed on charcoal medium without any plant growth regulators. This promotive effect of a growth regulator free medium on in vitro root induction has been recorded in other trees such as Robinia pseudoacacia (Kanwar et al 2009) and Morus alba (Agarwal and Kanwar 2007). Plant Cell Tiss Organ Cult (2010) 100:199-207 205 Acclimatization of in vitro raised plantlets…”
Section: Influence Of Agno 3 On Shoot Bud Regenerationmentioning
confidence: 92%
“…In addition, gynogenic haploids of M. alba were obtained by culturing unpollinated ovaries (Thomas et al 1999), triploid plants were regenerated from immature endosperm (Thomas et al 2000) and tetraploids were produced from apical buds following colchicine treatments (Chakraborti et al 1998). Somatic embryogenesis from mature zygotic embryos and the development of an efficient secondary embryogenic system have also been reported (Agarwal et al 2004;Agarwal and Kanwar 2007). On the other hand, black mulberry is a somewhat difficultto-propagate species, as it tends to bleed heavily when cut.…”
Section: Introductionmentioning
confidence: 98%